Overview of Knowledge and Behavior of University of Mataram Students Regarding Proper Medication Disposal - Rifqi Rizqullah; Mahacita Andanalusia; Lale Justin Amelinda Elizar (Jurnal Biologi Tropis, 2026)
Incorrectly throwing away unused or expired drugs can negatively impact the environment and public health by causing pollution. College students, who frequently take medications on their own and keep them, might add to this issue. This study aims to assess the knowledge and disposal behavior of students at Universitas Mataram regarding proper medication disposal practices. This study employed a descriptive quantitative design with a cross-sectional approach. Data were collected online from 428 respondents selected through purposive sampling using the ReDiUM (Return and Disposal of Unused Medications Questionnaire). Data were analyzed using descriptive univariate analysis to determine the frequency distribution and percentage of respondents’ knowledge and behavior categories related to medication disposal practices. The results showed that most respondents had a low level of knowledge regarding proper medication disposal, while only a small proportion demonstrated high knowledge. In terms of behavior, the majority of respondents exhibited moderate disposal practices, whereas good disposal behavior was found in fewer respondents. These findings indicate that students’ understanding and practices regarding proper medication disposal are still not optimal. In conclusion, Universitas Mataram students generally demonstrated insufficient knowledge and moderate behavior regarding proper medication disposal. This condition highlights the need for educational interventions and awareness programs related to pharmaceutical waste management among university students. Practical implications of this study include the development of campus-based health promotion programs, medication take-back campaigns, and public health education initiatives to encourage environmentally safe medication disposal practices.